Increasing Indian Influence in Afghanistan: Impacts on Pakistan - Majeed, Tabassum; Bashir, Faiza (Annals of Human and Social Sciences, 2023)
The objective of this study is to delve into the factors that are leading to increased Indian involvement in Afghanistan and how they are impacting Pakistan. Afghanistan's geographical location at the intersection of Central, Middle, and South Asia has led to heightened Indian strategic engagement, which has consequently affected its relationship with Pakistan. Various variables shape India's foreign policy, including its aspiration for access to Central Asian Republics. India's geographical proximity has resulted in substantial setbacks for Pakistan, leading to Pakistan surpassing the United States as the primary contributor to Afghanistan. The study, employing qualitative methods, argues that Pakistan's domestic security is jeopardized by India's influential soft power in Afghanistan. India's engagement extends not just to Central Asia but also within its own borders, as its Afghan strategy seeks to get access to energy resources. It is found that India views the Afghan War as a chance to offset Pakistan's dominance in the area and recommends that the US take into account the circumstances and stabilize Afghanistan.